(untitled) (Baghdad Science Journal, 2011)
Primary productivity and chlorophyll-a were used in this study to monitor the restoration process of southern Iraqi marshes (Al-Hewaizeh, central marshes, and Al-Hammar). The phytoplankton primary productivity was based on oxygen light/dark bottle method. Two different depths samples were taken monthly from six studied marshes stations (two stations for each marsh) during November 2005 to October 2006, while chlorophyll-a samples taken from surface water. The phytoplankton primary productivity values ranged 9.38 – 249.79 mg C/m3.hr for all marshes, its values for surface water sample ranged 11.71 – 256.24 mg C/m3.hr, while for 1m depth ranged 9.38 – 142.5 mg C/m3.hr. Chlorophyll-a values ranged between (1.1 – 21.26) µg/l indicating high values of productivity in the studied marshes comparing with other aquatic Iraqi ecosystems. Also, dissolved oxygen and oxygen saturation rate were measured in this study.